Transforming polymer blends into composites : a pathway towards nanostructured materials - Denchev, Z. (2008)
Polymer blends and polymer-based composites are two of themost rapidly developing groups of materials being of industrial, as well as of academic, interest. More than a decade ago a new group of polymer materials was introduced, which became known under the name ‘microfibrilar composites’ (MFCs). They were obtained by the transformation of blends of thermoplastic polymers into micro- or nanostructured systems by combination of appropriate mechanical and thermal treatments. Since then, the importance of these novel materials, both for theory and for engineering practice, has increased significantly. It is an objective of this review to outline the place of MFCs within the whole variety of polymer-based composites. Furthermore, the methods of their preparation, the ways of investigating their structure and the relation of the structure and mechanical properties are discussed. Ultimately, an evaluation of the future trends in this exiting interdisciplinary research field is attempted.